The educational possibilities of Augmented Reality - Julio Cabero Almenara; Julio Barroso Osuna (Springer, 2016)
A large number of emergent technologies have been acquiring a strong impulse in recent years. One of these emergent technologies is Augmented Reality (RA), which will surely have a high level of penetration into all our educational centers, including universities, in the next 3 to 5 years, as a number of different reports have already highlighted. The present paper shows various elements which, in our opinion, play an essential role when it comes to the incorporation of Augmented Reality into teaching, stressing the fact that this incorporation should not entail a technological problem but an educational and didactic issue. A mention is additionally made of several studies which have been performed with regard to the didactic exploitation of this emergent technology, as well as to the potential that it offers us. Our study forms part of an R&D&I initiative undertaken within the framework of the Plan Estatal de Fomento de la Investigación Científica y Técnica de Excelencia 2013-2016 [2013-16 State (National) Plan for the Promotion of Excellence Scientific and Technical Research], with reference EDU2014-57446-P.